98.6k views
0 votes
IM REALLY CONFUSED, please help

A. Given the equation 6(x + 3) = 3x − 3, solve for the variable. Explain each step and justify your process.
B. Jeff solved a similar equation below. Is Jeff's solution correct? Explain why or why not.
5x − 2 = 3(x + 2)
5x − 2 = 3x + 6
8x = 8
x = 1

1 Answer

5 votes
6(x + 3) = 3x - 3 Given
6x + 18 = 3x - 3 Distribute the 6
6x = 3x - 21 Subtract 18 from both sides
3x = - 21 Subtract 3x from both sides
x = -7 Divide both sides by 3

5x - 2 = 3(x + 2)
5x - 2 = 3x + 6
5x = 3x + 8
2x = 8
x = 4

Jeff's solution is incorrect; his solution is incorrect because he added 3x to the left side when he should have subtracted it to cancel it from the right side.

Hope this helps.
User Anorak
by
5.7k points